2011
DOI: 10.1590/s1516-35982011000800026
|View full text |Cite
|
Sign up to set email alerts
|

Zona de conforto térmico de ovinos da raça Santa Inês com base nas respostas fisiológicas

Abstract: RESUMO -Objetivou-se estabelecer a zona de conforto térmico para ovinos da raça Santa Inês por meio da comparação das respostas fisiológicas em diferentes opções de temperatura em câmara bioclimática. O experimento teve duração de 71 dias e foi conduzido utilizando-se sete borregas da raça Santa Inês por tratamento. Os tratamentos foram as faixas de temperatura de 10, 15, 20, 25, 30, 35 e 40°C, com três repetições (dias de exposição) e cinco dias de intervalo. O delineamento experimental utilizado foi o inteir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
2
13
0
17
Order By: Relevance
“…Pereira et al (2014) stated that climatic conditions of the Gurguéia Valley region produced significant changes in the physiological parameters of Morada Nova and Santa Inês sheep on concentrate supplementation, which can affect the behaviour patterns of these sheep owing to the heat increment. Eustáquio Filho et al (2011) reported that an environment with a temperature of 25 ºC and a humidity of 65% reflects the best conditions of comfort for sheep and animal productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Pereira et al (2014) stated that climatic conditions of the Gurguéia Valley region produced significant changes in the physiological parameters of Morada Nova and Santa Inês sheep on concentrate supplementation, which can affect the behaviour patterns of these sheep owing to the heat increment. Eustáquio Filho et al (2011) reported that an environment with a temperature of 25 ºC and a humidity of 65% reflects the best conditions of comfort for sheep and animal productivity.…”
Section: Resultsmentioning
confidence: 99%
“…A produção de ovinos em região tropical do Brasil pode levar os animais ao estresse calórico, o qual é um fator que limita a produção de ovinos e sua causa está correlacionada com as altas temperaturas ambiente, desta forma o ajuste da prática de manejo, horário de arraçoamento da dieta, quantidades de refeições, utilização de ambiente com sombra podem ocasionar melhora no sistema de produção (NEIVA et al, 2004;NEVES et al, 2009), além do controle mais preciso das variáveis ambientais como temperatura do ar, umidade relativa do ar e velocidade do vento (EUSTÁQUIO FILHO et al, 2011).…”
Section: Introductionunclassified
“…The results fell within the range of thermal comfort (10°C-25°C), indicating that the animals were not under thermal stress (EUSTÁQUIO FILHO et al, 2011).…”
Section: Methodsmentioning
confidence: 67%